Art and Narrative in Reog Ponorogo: Collaboration of Oral Tradition and Performance as Cultural Heritage - Purnani, Siwi Tri; Azizah, Hilma Azmi (Universitas Pahlawan Tuanku Tambusai, 2025)
This research focuses on the cultural expressions of Ponorogo district manifested in two main dimensions: oral literature and the performing art of Reog Ponorogo. Oral literature in Ponorogo has an important role in maintaining tradition and history, while Reog Ponorogo as a performing art form depicts local values and mythologies that are passed down through generations. This study aims to analyze the relationship between the two cultural dimensions in shaping the identity of the Ponorogo community, as well as the challenges of modernization that affect its sustainability. This study uses a qualitative method with an ethnographic approach that allows researchers to understand the Ponorogo culture deeply from the perspective of the local community. Based on field studies and existing literature, this article concludes that these two cultural expressions support each other and become an integral part of the cultural identity of the Ponorogo Regency. Using a qualitative and ethnographic approach, this article will examine how these two cultural dimensions interact with each other in shaping Ponorogo's distinctive cultural identity.